'Smart speaker, tell me about your acoustic sensor'. (February 2021) - Knight, Pip
Abstract : Smart speakers that can register our everyday commands have become commonplace in homes around the world. While the acoustics sensors inside these devices are far flung from the first microphone, the technology is still evolving, as Pip Knight explains